A preliminary study of the association between Blastocystis and quantification of selected yeasts in IBD and IBS patients - Khosravany, Zohre; Khodavaisy, Sadegh; Olyaiee, Alireza; Sadeghi, Amir; Nemati, Sara; Shahrokh, Shabnam; Mohammad Ali Gol, Sara; Shojaei, Sajad; Mohammad Rahimi, Hanieh; Mirjalali, Hamed (Frontiers in Medicine, 2025)
ObjectiveIrritable bowel syndrome (IBS) and inflammatory bowel disease (IBD) are gastrointestinal disorders, which can be triggered by gut microbiota dysbiosis. The development of IBS-like symptoms has been linked to the overgrowth of Candida spp. In addition, the critical role of fungi has been highlighted in the pathogenesis of IBD. This study investigated the association between Blastocystis and selected yeasts in IBS and IBD patients.MethodsThis investigation is a cross-sectional study from 2022 to 2024, performed on 91 participants, including 20 healthy individuals, 27 patients with IBS, and 44 IBD patients [39 with ulcerative colitis (UC; 88.63%) and 5 (11.37%) Crohn’s disease (CD)], who were also categorized based on the presence of Blastocystis. Total DNA was extracted from stool samples, and the presence and quantity of yeasts including C. albicans, C. tropicalis, C. glabrata, C. parapsilosis, C. krusei, Geotrichum candidum, Rhodotorula spp., Cryptococcus neoformans, and Saccharomyces cerevisiae were evaluated by real-time PCR. Statistical tests were used to assess significant associations between variables.ResultsSaccharomyces cerevisiae and C. albicans were the most prevalent yeasts in all groups. Candida tropicalis and C. neoformans were identified in neither patients nor healthy subjects. The presence/absence of C. albicans was not significantly different between patients with IBD, IBS, and the control groups. This was similar for G. candidum. However, there was a difference in the presence of S. cerevisiae among patients, although it was insignificant (p-value = 0.077). There was a significant difference in the quantity of C. albicans between IBD (880.421 ± 2140.504), IBS (10.307 ± 15.206), and controls (2875.888 ± 8383.889) (p-value = 0.020). Specifically, the source of difference was seen between IBD patients and the control group (p-value = 0.005). In addition, considering the presence of Blastocystis, a statistically significant association was seen between the number of C. albicans and the sample groups (p-value = 0.013). The quantity of C. albicans was significantly different between IBS and IBD patients.ConclusionRegarding the presence of Blastocystis, the quantity of C. albicans and S. cerevisiae was increased and decreased in the studied groups, respectively. This is a preliminary study, and eukaryote–eukaryote association in IBS and IBD patients should be considered in further studies.